Elevation of extracellular adenosine mobilizes haematopoietic progenitor cells and granulocytes into peripheral blood and enhances the mobilizing effects of granulocyte colony-stimulating factor - Hofer, M; Weiterová, L; Vacek, A; Znojil, V; Pospísil, M; Vácha, J (European journal of haematology, 2003)
We tested the capabilities of drugs elevating extracellular adenosine and of granulocyte colony-stimulating factor (G-CSF), given alone or in combination, to mobilize haematopoietic progenitor cells for granulocytes and macrophages (GM-CFC) and granulocytes into peripheral blood. Elevation of extracellular adenosine was induced by joint administration of dipyridamole (DP), a drug inhibiting the cellular uptake of adenosine, and adenosine monophosphate (AMP) serving as an adenosine prodrug. DP + AMP, G-CSF or all these drugs in combination were administered either singly or repeatedly in a 4-d treatment regimen. Elevation of extracellular adenosine was found to mobilize significantly both GM-CFC and granulocytes after both single and repeated administration of DP + AMP. These results show that the elevation of extracellular adenosine presents a potent mechanism for mobilization of GM-CFC and granulocytes into the blood. When the combination of DP + AMP + G-CSF was given under the 4-d regimen, the mobilizing effects of its administration were additive when compared with those of DP + AMP alone or G-CSF alone. The observed ability of the drugs elevating extracellular adenosine to enhance the mobilizing action of G-CSF points out possible practical utilization of the findings presented here. This conclusion is further supported by the results of an additional experiment which indicate that blocking of haemodynamic side effects of drugs elevating extracellular adenosine by noradrenaline does not suppress their mobilizing effects.
Keywords: adenosinmonofosfát; Cell Movement; extracelulární prostor; myši inbrední C57BL; mužské pohlaví; Granulocytes; Mice; adenosin; myši inbrední CBA; granulocyty; Extracellular Space; Adenosine Monophosphate; počet buněk; faktor stimulující kolonie granulocytů; Macrophages; Adenosine; zvířata; pohyb buněk; Dipyridamole; myši; makrofágy; Mice, Inbred CBA; Granulocyte Colony-Stimulating Factor; hematopoetické kmenové buňky; Cell Count; Hematopoietic Stem Cells; dipyridamol; Mice, Inbred C57BL; Male; Animals